Inhibition of extracellular signal-regulated kinase downregulates endoplasmic reticulum stress-induced apoptosis and decreases brain injury in a cardiac arrest rat model - Yuan, Z-L; Zhang, Z-X; Mo, Y-Z; Li, D-L; Xie, L; Chen, M-H (Physiological research, 2022)
Cerebral ischemia-reperfusion injury (CIRI) is the predominant cause of neurological disability after cardiac arrest/cardiopulmonary resuscitation (CA/CPR). The endoplasmic reticulum stress (ERs)-induced apoptosis plays an important role in neuronal survival/death in CIRI. Our previous studies reported that the extracellular signal-regulated kinase (ERK) inhibitor, PD98059, alleviates CIRI after CA/CPR. Whether ERs-induced apoptosis is involved in the neuroprotection of PD98059 remains unknown. This study aims to investigate the effects of ERK inhibition by PD98059 on ERs-induced apoptosis after CIRI in the CA/CPR rat model. The baseline characteristics of male adult Sprague-Dawley (SD) rats in all groups were evaluated before CA/CPR. The SD rats that survived from CA/CPR were randomly divided into 3 groups (n=12/group): normal saline group (1 ml/kg), dimethylsulfoxide (DMSO, the solvent of PD98059, 1 ml/kg) group, PD98059 group (0.3 mg/kg). Another 12 SD rats were randomly selected as the Sham group. Twenty-four hours after resuscitation, neural injury was assessed by survival rate, neurological deficit scores (NDS) and Nissl staining; apoptosis of brain cells was detected using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining; mRNA expression and protein levels of ERs-related protein BIP, PERK, ATF4 and CHOP were checked with RT-PCR and Western Blot. The results showed that there were no significant differences in baseline characteristics before CA/CPR among all groups. PD98059 significantly improved survival rate and NDS, increased the Nissl bodies in neurons, reduced apoptosis, downregulated the mRNA transcription and expression levels of BIP, PERK, ATF4 and CHOP at 24 h after CA/CPR. Our results demonstrate that inhibition of ERK by PD98059 alleviates ERs-induced apoptosis via BIP-PERK-ATF4-CHOP signaling pathway and mitigates CIRI in the CA/CPR rat model.
Keywords: Animals; RNA, Messenger; Reperfusion Injury; stres endoplazmatického retikula; Extracellular Signal-Regulated MAP Kinases; potkani Sprague-Dawley; Heart Arrest; poranění mozku; zvířata; messenger RNA; Brain Injuries; extracelulárním signálem regulované MAP kinasy; Rats, Sprague-Dawley; reperfuzní poškození; Rats; Apoptosis; Male; apoptóza; krysa rodu Rattus; srdeční zástava; Endoplasmic Reticulum Stress; mužské pohlaví